Investigação da hidroxiapatita como matriz suporte em análise multielementar por LA-ICP-MS - Neves, Vinicius Machado (2022)
This study investigated the applicability of calcium hydroxyapatite (HA) as a support matrix for laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) multi-element quantitative analysis. HA pellets were prepared and fortified with 5.0 µg g-1 of Ag, Al, As, B, Ba, Be, Bi, Cd, Co, Cr, Cu, Fe, K, Li, Mg, Mn, Mo, Na, Ni, Pb, Rb, Sb, Se, Sn, Sr, Ti, Tl, U, V and Zn. The following operating parameters of the LA-ICP-MS system were optimized: energy, laser beam diameter and scanning rate, as well as carrier gas flow rate. Aiming a multi-element quantification, the best analysis conditions were: 80% energy, laser beam diameter of 150 µm, scanning rate of 150 µm s-1 and carrier gas (Ar) flow rate of 1.15 L min-1 , since this arrangement showed feasible results regarding signal/noise ratio for the largest number of elements. Considering that the laser interaction depends on the composition of the sample matrix, internal standards (IS) were evaluated in order to correct possible non-spectral interferences. For this purpose, the following elements were chosen: Ca and P, naturally present in HA, and Au, Ga, Ge, In, Ir, Rh and Sc, fortified to 5.0 µg g-1 . Calibration curves ranged from 0.25 to 10.0 µg g-1 for each analyte, and were linear, with R² superior to 0.99 for 17 elements, for 8 elements used as IS. The quantification limits varied from 25 ng g-1 for 205Tl/193Ir to 4,76 µg g-1 for 60Ni/193Ir. The method was applied to fertilizers, rhyolite and granite, which are inorganic matrices. The obtained results were compared to reference values. Quantitative analyses of As, Ba, Cd, Cu, Mo, Ni, Pb, U and V were achieved in fertilizers; As, Bi, Cu, Li, Mo, Ni, Pb, Sb, Sn, Rb, Tl and U in rhyolite; and Ba, Bi, Co, Li, Pb, Rb, Sn, Tl and U in granite, with concordance ranging from 75 to 120% in relation the reference values. The applicability of the IS depends on the analyte and sample matrix characteristics.